Polymer Supported Directed Differentiation Reveals a Unique Gene Signature Predicting Stable Hepatocyte Performance. Issue 12 (24th June 2015) - Villarin, Baltasar Lucendo; Cameron, Kate; Szkolnicka, Dagmara; Rashidi, Hassan; Bates, Nicola; Kimber, Susan J.; Flint, Oliver; Forbes, Stuart J.; Iredale, John P.; Bradley, Mark; Hay, David C.
<x xml:space="preserve">Abstract</x> In theory, pluripotent stem cells can give rise to all somatic cell types found in the human body. The ability to generate renewable sources of human cells has enormous potential to improve human health and wealth. One major obstacle to the routine deployment of stem cell–derived cells is their instability in culture. To tackle this issue a synthetic polymer surface is used.